3D automatic target recognition for missile platforms - Kechagias Stamatis, Odysseas (Cranfield University, 2017)
The quest for military Automatic Target Recognition (ATR) procedures arises from the demand to reduce collateral damage and fratricide. Although missiles with two-dimensional ATR capabilities do exist, the potential of future Light Detection and Ranging (LIDAR) missiles with three-dimensional (3D) ATR abilities shall significantly improve the missile’s effectiveness in complex battlefields. This is because 3D ATR can encode the target’s underlying structure and thus reinforce target recognition. However, the current military grade 3D ATR or military applied computer vision algorithms used for object recognition do not pose optimum solutions in the context of an ATR capable LIDAR based missile, primarily due to the computational and memory (in terms of storage) constraints that missiles impose. Therefore, this research initially introduces a 3D descriptor taxonomy for the Local and the Global descriptor domain, capable of realising the processing cost of each potential option. Through these taxonomies, the optimum missile oriented descriptor per domain is identified that will further pinpoint the research route for this thesis. In terms of 3D descriptors that are suitable for missiles, the contribution of this thesis is a 3D Global based descriptor and four 3D Local based descriptors namely the SURF Projection recognition (SPR), the Histogram of Distances (HoD), the processing efficient variant (HoD-S) and the binary variant B-HoD. These are challenged against current state-of-the-art 3D descriptors on standard commercial datasets, as well as on highly credible simulated air-to-ground missile engagement scenarios that consider various platform parameters and nuisances including simulated scale change and atmospheric disturbances. The results obtained over the different datasets showed an outstanding computational improvement, on average x19 times faster than state-of-the-art techniques in the literature, while maintaining or even improving on some occasions the detection rate to a minimum of 90% and over of correct classified targets.